Blood cytokines as potential predictors of therapy effectiveness in patients with moderate to severe psoriasis treated with the IL-12/IL-23 inhibitor ustekinumab - Arfenya E. Karamova; Anastasiia A. Vorontsova; Alexandr А. Nikonorov; Evgenia R. Nikonorova; Аlexey A. Kubanov (Vestnik Dermatologii i Venerologii)
Background. Despite the proven efficacy and safety of biologics in the treatment of psoriasis (Ps), a number of patients experience heterogeneity in response to therapy in both the short-term and long-term perspectives.